Describing the Adsorption of Pb\(^2\)+, Cu\(^2\)+, Ni\(^2\)+, Zn\(^2\)+, Cr\(^6\)+, and Cd\(^2\)+ from a Synthetic Acid Mine Drainage onto Chitosan Derivative in a Packed Bed Column: Analysis through Mathematical Modeling - Igberase, Ephraim; Mkhize, Innocentia G. (Chemical and Materials Sciences: Research Findings Vol. 3, 2025)
Studies on the adsorption of metal ions in batch mode using modified chitosan beads have been reported by several authors in the literature. Consequently, packed bed column studies are performed for large-scale operations to generate data directly applicable to real wastewater treatment. For packed column adsorption, how to predict the breakthrough curve is a vital issue because it gives the necessary information for the design of a packed column adsorption system. This work investigated the application potential of chitosan derivatives for the uptake of Pb2+, Cu2+, Ni2+, Zn2+, Cr6+, and Cd2+ ions from aqueous solution in a packed bed adsorption column. On this note, the adsorbent was characterised by Fourier transform infrared spectroscopy (FTIR) and Scanning electron microscope (SEM), the effect of breakthrough parameters such as influent concentration (10, 20, and 30 mg/L), bed height (21, 28 and 35 cm) and feed flow rate (10, 15 and 20 ml/min) were determined. The experimental data were fitted to mathematical column models: Bed Depth Service Time (BDST), Yoon-Nelson, and the Thomas model. The adsorption of metal ions in a packed bed column is highly affected by the quantity of adsorbent applied. The flow rate in a continuous flow adsorption column plays a vital role as it controls the retention time during which the adsorbate contacts the adsorbent surface. The removal efficiency, breakthrough, and exhaustion time increased with an increase in bed height but decreased with an increase in flow rate and influent concentration. The mathematical models applied in this study were successful in describing experimental data. Desorption studies were performed with no loss in the mass of the beads, and the breakthrough and exhaustion times were found to be the same on reusing the beads.